PERENCANAAN BLUEPRINT JARINGAN KOMPUTER BERBASIS INTER-VLAN ROUTING PADA SMKN 3 PUJUT - Putra, Dea Pratama (Pusat Riset dan Inovasi Nasional, 2022)
The lack of access to the internet network in schools is a factor in the slow teaching and learning process, because the lack of wireless signal coverage also causes the school community to only gather at one point. In an effort to deal with this problem, researchers built an inter-vlan network blueprint with wireless hotspots, in order to improve network performance and network security. In the process of building an inter-vlan network blueprint with a mikrotik hotspot, using the ppdioo method, among others, prepare preparation, plan plan, design design, implement, operate, optimize optimization. From the results of this study, in building a blueprint for an inter-vlan network with a mikrotik hotspot, we get the appropriate results from the initial plan. Which can improve network performance and expand access to internet network coverage.